Dark sky tourism: economic impacts on the Colorado Plateau Economy, USA. Issue 4 (25th September 2019) - Mitchell, David; Gallaway, Terrel
Abstract : Purpose: This paper aims to examine the economic impact from dark-sky tourism in national parks in the USA on the Colorado Plateau. The Colorado Plateau is a region encompassing parts of Arizona, Colorado, New Mexico and Utah that is known for its dark, star-filled night skies. Tourists in national parks are increasingly interested in observing this natural recreational amenity – especially considering that it is an ecological amenity that is quickly disappearing from the planet. Using a 10-year forecast of visitors to the national parks and using standard input-output modeling, it is observed that, for the first time anywhere, the value of dark skies to tourism in this area. The authors find that non-local tourists who value dark skies will spend $5.8bn over the next 10 years in the Colorado Plateau. These tourist expenditures will generate $2.4bn in higher wages and create over 10, 000 additional jobs each year for the region. Furthermore, as dark skies are even more intense natural amenity in the non-summer months, they have the ability to increase visitor counts to national parks year-round and lead to a more efficient use of local community and tourism-related resources throughout the year. Design/methodology/approach: Using a 10-year forecast of visitors to the national parks and using standard input-output modeling, we find that non-local tourists who value dark skies will spend $5.8bn over the next 10 years in the Colorado Plateau. Findings: These tourist expenditures will generate $2.4bn in higher wages and create over 10, 000 additional jobs each year for the region. Furthermore, as dark skies are even more intense natural amenity in the non-summer months, they have the ability to increase visitor counts to national parks year-round and lead to a more efficient use of local community and tourism-related resources throughout the year. Originality/value: To the best of the authors' knowledge, no other study has attempted to value the environmental amenity of dark skies.